The challenges facing by expatriate – a case study in Maju Holdings Sdn Bhd / Azizul Syawal Idham Shamsul Ambia - Shamsul Ambia, Azizul Syawal Idham (Faculty of Business and Management, 2010)
This study is focus on the challenges facing by the expatriate that faced in the organization of Maju Holding Sdn Bhd. The main objective of this project paper is identifying the main challenges that the expatriate in the organization are faced. The research is focusing on expatriate employees at Maju Holding Sdn Bhd in all departments. The element that contribute to this problem are attitude of Malaysians, cross-culture challenges, custom and religions, addressing social status and gender. All the data was collected using primary data which is from interviewing and observation and secondary data which is from company annual report and journal that are related.